Предмет: Алгебра,
автор: Dead2016j
Решить СР
Вариант №1
Представьте в виде многочлена:
(2а + 7b)² =
(3a – 4b)² =
Вычислите:
39² = 71² =
Упростите:
(2a – 3b)² - 3b (3b - 4а) =
(a – 3)² + (6 - а)² + 2 (a – 3)(6 – а)=
Ответы
Автор ответа:
1
Ответ:
(2а+7b)^2 = 4a^2+28ab+49b^2
(3a-4b)^2 = 9a^2-24ab+16b^2
39^2 = 1521
71^2= 5041
Упростите:
(2a-3b)^2-3b(3b-4a) = 4a^2-12ab+9b^2-9b^2+12ab = 4a^2
(a-3)^2+(6-a)^2+2(a-3)(6-a) = a^2-6a+9+36-12a+a^2+12a-36 = 2a^2-6a+9
Объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: img
Предмет: Другие предметы,
автор: Камила5487
Предмет: Русский язык,
автор: Викея
Предмет: Математика,
автор: ivanova53
Предмет: Математика,
автор: Анна170716
Вычислите:
39² =
71² =